Control of Cosmopolites sordidus (Coleoptera:Curculionidae) with entomopathogenic fungi Beauveria bassiana and Metarhizium anisopliae in banana cultivation - Moreira, Francisco José Carvalho; Araújo, Beatriz de Abreu; Silva, Vanádia Farias da; Luna, Neyreane de Sousa; Araújo, Ozeládia Parente; Braga, Roberto Davi dos Santos (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2017)
The continuous use of pesticides promotes rapid and effective reduction of pests, however, this practice entails the pests the possibility of developing resistance by subjecting the farmer to change product constantly increase the dose or even mix or use more toxic products. Being Cosmopolites sordidus one beetle nocturnal that affect the banana tree because their larvae open galleries in its rhizome and lower pseudostem, resulting in decline, overturning and death of the plant. In view of this and the population’s awareness of this problem, the greater has been the participation of organic agriculture in food supply. In this context, this study aimed to evaluate the effect of two entomopathogenic fungi in control of C. sordidus in banana cultivation. The trial was held in lot E-104, the Irrigated Perimeter of Baixo Acaraú, in Marco, Ceará state. The statistical design was completely randomized, in factorial 2 x 5, two fungi (Beauveria bassiana and Metharizium anisopliae) in five concentrations (0, 5, 10, 15 and 20 g L-1), 5 repetitions each. We evaluated the number of insects for bait in each evaluation and the total number of captured insects. It was found that the fungus B. bassiana was more effective in controlling C. sordidus. It was also observed that the higher concentrations of 10, 15 and 20 g L-1 were more effective. We conclude that the biological control with B. bassiana can be used, as is shown adapted to climatic conditions in the study area.